CULINARY SKILLS IN HIGHER EDUCATION: A STUDY OF HOME ECONOMICS STUDENTS IN FEDERAL COLLEGES OF EDUCATION OMOKU, NIGERIA - Jane Chizoba , Nwosu (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
The study of home economics is a crucial component of higher education in Nigeria's colleges of education. It allows students to acquire the fundamental home education needed in modern societies. However, little is known about the culinary abilities of students taking home economics classes. The present study assessed the culinary skills of home economics students in the Federal College of Education Technical, Omoku, River State,t Nigeria. Ninety-seven students were recruited from home economics departments in colleges of education in the southeast. The respondents completed a self-report measure of cooking skills. The percentage analysis showed that most students (61.11%) enrolled in home economics possess high cooking skills. The findings from the study have implications for increased enrollment in home economics and effective implementation of policies geared towards the development of home economics in the colleges of education in Nigeria.